Exploring the Psychosocial Challenges Experienced by Teenage Student Mothers in Senior High Schools in Asene Manso Akroso District, Ghana. - Yelkpieri, Daniel; Bileman, Michael Nyabido; Namale, Matthew Kojo (Journal of Education and Practice, 2024)
Purpose: This study explored the psychosocial challenges experienced by teenage student mothers in senior high schools in Asene Manso Akroso District, Ghana. Methodology: The qualitative research approach was employed to understand and explore the psychosocial challenges experienced by teenage student mothers in senior high schools in Asene Manso Akroso District. Purposive sampling method was used to select the population of the study. Data saturation point was used to select a sample of twelve teenage student mothers from a population of fifty-five teenage student mothers from the two senior high schools in the district. Interview guide was used for the data collection and content analysis was used to analyse the data. Findings: The study revealed that teenage student mothers were ridiculed and rejected by their peers in school. It was also found that the teenage student mothers felt lonely and isolated as most of their friends shunned them for fear of being classified in the same category with teen mothers. Unique contribution to theory, practice and policy: It is therefore, recommended that guidance and counselling units in senior high schools should liaise with school authorities to provide academic and social support systems to help them adjust into the school system